2003
DOI: 10.1103/physrevlett.90.162501
|View full text |Cite|
|
Sign up to set email alerts
|

Na21(p,γ)Mg

Abstract: The 21Na(p,gamma)22Mg reaction is expected to play an important role in the nucleosynthesis of 22Na in oxygen-neon novae. The decay of 22Na leads to the emission of a characteristic 1.275 MeV gamma-ray line. This report provides the first direct measurement of the rate of this reaction using a radioactive 21Na beam, and discusses its astrophysical implications. The energy of the important state was measured to be E(c.m.)=205.7+/-0.5 keV with a resonance strength omegagamma=1.03+/-0.16(stat)+/-0.14(sys) meV.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
5
4
1

Relationship

4
6

Authors

Journals

citations
Cited by 99 publications
(19 citation statements)
references
References 20 publications
0
19
0
Order By: Relevance
“…In a one-zone post-processing study conducted with a Monte Carlo approach to rate variations, the 21 Na(p, γ ) reaction is given in a prioritized list of reactions that affect the production of 22 Na. 168,169 Using a 1-D hydrodynamic model, Bishop et al 179 and Davids et al 180 found that 22 Na production decreased by about 20% when results using two rates differing by a factor of ≈5 (at 0.2 GK) were compared. r 22 Na(p, γ ) 23 Mg Coc et al, using a semi-analytical approach, 165 compared the yield of 22 Na obtained using different 22 Na(p, γ ) rates.…”
Section: Thermonuclear Reaction Rates With Demonstrated Impact On Novmentioning
confidence: 99%
“…In a one-zone post-processing study conducted with a Monte Carlo approach to rate variations, the 21 Na(p, γ ) reaction is given in a prioritized list of reactions that affect the production of 22 Na. 168,169 Using a 1-D hydrodynamic model, Bishop et al 179 and Davids et al 180 found that 22 Na production decreased by about 20% when results using two rates differing by a factor of ≈5 (at 0.2 GK) were compared. r 22 Na(p, γ ) 23 Mg Coc et al, using a semi-analytical approach, 165 compared the yield of 22 Na obtained using different 22 Na(p, γ ) rates.…”
Section: Thermonuclear Reaction Rates With Demonstrated Impact On Novmentioning
confidence: 99%
“…The 22 Na yield predicted by nova models is sensitive to the thermonuclear rates of the reactions associated with explosive hydrogen burning on the surface of a white-dwarf star accreting hydrogen-rich material from a binary companion star [19,32]. This has motivated the development of innovative experimental nuclear physics techniques, providing rates to improve predictions of the 22 Na yield [33][34][35][36][37][38][39][40][41][42][43][44][45]. While 22 Na is being produced during the thermonuclear runaway driving a nova, the 22 Na(p, γ ) 23 Mg reaction is actively destroying it.…”
mentioning
confidence: 99%
“…where 𝜂 = 𝜂 cs 𝜂 t 𝜂 det 𝜂 𝛾 and, for the cases under consideration below, we estimate 𝜂 cs = 0.25 (Shima et al 1992), 𝜂 t = 1, 𝜂 det = 1, and 𝜂 𝛾 = 0.5 (Bishop et al 2003;Christian et al 2013;Christian et al 2018).…”
Section: Implications For Resonance Strength Measurementsmentioning
confidence: 99%